A tour of animated forms in school education and workshops: the gaze of female researchers: (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
his article aims to provide information to enrich the knowledge of the role of women who have established links in animation theater, school education and non-formal education. Forthis purpose, an analysis is carried out based on a corpus available at the Centre de Recherche et de Documentation of the Institut International de la Marionnette in Charleville-Mézières (TheResearch Centre at the International Puppet Institute in Charleville-Mézières) collected in February 2020. The selection criteria include research performed during the 20th Century to the present and conducted by female researchers. A limited sample was obtained, however, it makes possible to specify the bibliographic material available in one of the most important documentation centers of puppet features theater in the world.